Peran Korban Pemerkosaan Dalam Membantu Proses Penyidikan - Christy Tanasale; Elsa Rina Maya Toule; Margie Gladies Sopacua (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Rape is one of the most common crimes in society.Purposes of the Research: The purpose of this study is to analyze and discuss the role of the victim in revealing the perpetrators of the crime of rape in the investigation stage and legal protection for victims of rape in the investigation process. Methods of the Research: In this legal research, the author uses normative juridical legal research which obtains data from literature studies in the form of laws, documents, books, magazines and other literature related to writing.Results of the Research: The results of this study indicate that the role of rape victims in the investigation stage is when the victim dares to report, the victim is open and the victim is cooperative and the victim includes clear information, because the role of the victim is very influential in the investigation process. For this reason, there is legal protection for rape victims, where victims get legal protection which is quite clearly stated in Law Number 31 of 2014. As well as other protections such as Juridical Protection, Psychological Protection and Social Protection. So, the authorities can take protective measures for victims and sanctions for perpetrators in accordance with the provisions of applicable regulations.